Lending Rationale of Financial Institution and Fintech on the Perception of Borrowers: A Qualitative Study - Anwar, Mokhamad; Nidar, Sulaeman Rahman; Widianto, Sunu; Layyinaturrobaniyah, Layyinaturrobaniyah (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2021)
The development of Financial Institutions including Financial Technology (Fintech) in providing loans to borrowers is increasingly important in the current business financing system. This study aims to determine the perceptions of borrowers by exploring their views on lending practices pro- vided by financial institutions and fintech and identifying the factors that influence the institution’s decision to provide loans to them. This study uses a qualitative research method by asking a number of questions to debtors in one of the Micro and Small and Medium Enterprises (MSMEs) commu- nities in the city of Bandung, Indonesia. The questionnaire form is in the form of open-ended ques- tions and is distributed to 47 MSMEs in the city with various types of business fields. The results show that the factors that influence the success of borrowers in obtaining credit from both financial institutions and fintech are the factors classified as 5 Cs of credit in terms of Character, Capacity, Capital, Collateral, and Conditions. All these factors are summarized as soft information and hard information, which are applied by financial institutions and financial technology institutions.